Using Electrical Impedance Myography as a Biomarker of Muscle Deconditioning in Rats Exposed to Micro- and Partial-Gravity Analogs - Semple, Carson; Riveros, Daniela; Sung, Dong-Min; Nagy, Janice A.; Rutkove, Seward B.; Mortreux, Marie (Frontiers in Physiology, 2020)
As astronauts prepare to undertake new extra-terrestrial missions, innovative diagnostic tools are needed to better assess muscle deconditioning during periods of weightlessness and partial gravity. Electrical impedance myography (EIM) has been used to detect muscle deconditioning in rodents exposed to microgravity during spaceflight or to standard ground-based models of hindlimb unloading using tail suspension (HU). Here, we used EIM to assess muscle changes in animals exposed to two new models: hindlimb suspension using a pelvic harness (HLS) and a partial weight-bearing (PWB) model that mimics partial gravity (including Lunar and Martian gravities). We also used a simple needle array electrode in lieu of surface or ex vivo EIM approaches previously employed. Our HLS results confirmed earlier findings obtained after spaceflight and tail suspension. Indeed, one EIM measure, the phase-slope, previously reported as highly sensitive to change, significantly decreased after HLS (day 0: 14.60+-0.97, day 7: 11.03+-0.81 and day 14: 10.13+-0.55 |Deg/MHz|, p<0.0001), and was associated with a significant decrease in muscle grip force. Although EIM parameters such as 50 kHz phase, reactance, and resistance remained variable over 14 days in PWB animals, we identified major PWB-dependent effects at 7 days. Moreover, the data at both 7 and 14 days correlated to previously observed changes in rear paw grip force using the same PWB model. In conclusion, our data suggest that EIM data have the potential to serve as biomarkers of muscle deconditioning during exposure to both micro- and partial- gravity during future human space exploration.